P471Site-specific shear stress-plaque severity relations by high axial resolution coronary profiling in an animal model of atherogenesis. (15th July 2014) - Pelosi, G; Panetta, D; Vozzi, F; Viglione, F; Filipovic, N; Savelijc, I; Exharcos, T; Trivella, MG; Parodi, O
Abstract: Purpose: Baseline low/oscillatory wall shear stress (WSS) is assumed to be a determinant of artery/site specificity of atherogenesis. However, different flow and plaque metrics, spatial resolution and imaging co-registration accuracy may lead to different results in correlating site-specific WSS values and lesion probability/size. In this study we compared, by high resolution histology-validated ex vivo microCT coronary profiling, baseline and end-diet maximal and mean WSS values averaged at 2 different axial thickness in a hypercholesterolemic swine model of atherogenesis. Methods: In pigs on high fat diet, an IVUS catheter (20 MHz, 100, 200 μm axial resolution, 5 mm penetration) has been advanced in distal left anterior descending artery (LAD), coronary Doppler flow velocity measured, and resulting 2D tomographic sections used to obtain 3D reconstruction for WSS estimate. WSS coronary profiling was obtained before and after 4 wks hypercholesterolemic diet. En bloc formalin fixed LAD was analysed by micro-CT scanner at 57.4 μm3 voxel resolution (up to 1300 consecutive cross-sections) and then processed for histomorphometry. 3D curved multi-planar reformation (MPR), image segmentation and 3D volume rendering allowed registration between microCT and IVUS cross-sectional frames at 120-130 corresponding sites. Coronary profiling of slice-averaged maximal and mean values of baseline and end-diet WSS and microCT plaque area (LA) and maximal intimal thickness (IT), validated by histomorphometry, were compared. Results: Statistically significant relations were found between 1. Plaque location and baseline WSS mean values at low resolution 2. Baseline WSS values and LA and IT of developed plaque at corresponding sites at low resolution 3. Baseline and end-diet diet mean and maximal WSS and LA(or IT) of mild/minimal intima changes (ATS initiation) at high resolution 4. End-diet maximal WSS values and plaque LA (or IT) at sites corresponding to the upstream slope of atheroma at high resolution. Conclusions: These findings confirm the higher incidence of atherogenesis at lower WSS sites within a single artery also suggesting that in the hypercholesterolemic swine model of atherogenesis, at higher spatial resolution of co-registered sections, 1. the overall inverse correlation between baseline WSS and plaque location/size becomes weaker 2. significant opposite wall geometry-related correlations are evidenced at different stages of developed lesions.